Factors affecting Women Micro Entrepreneurs and Sustainable Economic Development in Odisha - Tripathy, Dr. P.; Mohanty, Dr. A (IJRDO - Journal of Business Management, 2018)
Women entrepreneurial activity has tremendously contributed to socioeconomic impact on rural entrepreneurs especially female in Odisha. However, women benefited immensely from micro loans and facilitate their entrepreneurial activities in the country. Consequently, the paper intends to examine the microfinance factors that aid to women entrepreneurship development among the female borrower of the micro loans. The paper emphasizes the role women entrepreneurs played as the potentially emerging human resource in Odisha to overcome the socio-economic challenges in global perspective. Odisha Women are confined with domestic responsibilities rather than being educated, acquiring knowledgeable and be innovative. At the same time as few of them do parts of the overall population possess the capacity to transform rural economies into flourishing enterprises. High developing and lower middle economy have realized that developing women entrepreneurship is crucial to thrive as economically overriding nation in the technologically advanced world. Women sustainable development is a critical one toward rural economic transformation and growth for any country; therefore the economic sustainability of women entrepreneurship program is vital and challenging one to stakeholders and policy makers. Credit association (ROSCA) enable rural female entrepreneurs to develop their business activities especially in micro enterprises (MSEs). However, ROSCA women are mostly connected with Micro – Entrepreneurship activities. Very few are linked with Small Scale Enterprises. Those women continue to help in boosting a sustainable economy for themselves and provide job opportunities for others women. The rural women entrepreneurs with the sustainable economic development are able to contribute to the families, and increase per capital head. The present study deals with role of women’s economic development, contemporary perspective of women in ROSCA opportunities and factors responsible for the limitation of rural female entrepreneurs. This study tries to bring to light that women’s sustainable development is predestined and possible with government support.